141k views
3 votes
I need help with this please

I need help with this please-example-1
User Arun Redhu
by
6.9k points

1 Answer

0 votes

Answer:


y = x^2 + 6x + 8

Explanation:

The equation can be written using information from the graph. The vertex of the parabola is (-3,-1). Use the vertex form
y = a(x-h)^2 + k by substituting h = -3 and k = -1. The equation becomes
y = a(x--3)^2 + -1. It simplifies to
y = a(x+3)^2 - 1. To find a, substitute the point (x,y) on the graph into the equation and solve for a. Substitute x = -2 and y = 0.


0 = a(-2+3)^2 - 1


0 = a(1)^2 - 1


0 = a - 1


1 = a

So the equation is
y = (x+ 3)^2 - 1. Convert to standard form by distributing the parenthesis and combining like terms.


y = (x+ 3)^2 - 1\\y = x^2 + 3x + 3x + 9 - 1\\y = x^2 + 6x + 8

User Eugen Dimboiu
by
5.8k points